PENGARUH KOMPENSASI TERHADAP DISIPLIN KERJA PEGAWAI PADA BAGIAN UMUM SEKRETARIAT DAERAH KABUPATEN PANDEGLANG - Muhi Mukti; Reni Andriani (Universitas La Tansa Mashiro, 2018)
The research model used in this study is the method of observation, interviews, questionnaires, and literature studies conducted systematically based on purpose. The sample in this study were 84 people with an error rate of 5% according to the sampling technique based on calculations and Slovin formula. The analytical method used is Simple Linear Regression, Test Validity, Determination Coefficient and for hypothesis testing using the t test.From the results of the study show that each increase in compensation of 1 unit will affect the employee work discipline of 0.74 units, and compensation (Variable X) has a strong degree of relationship with employee work discipline (Y variable) of 0.79. Based on the calculation of the t test, it is obtained that tcount is greater than t table (11.72> 1.66365) then the null hypothesis is rejected, meaning that the effect of compensation on employee work discipline has a positive effect. This informs the influence of compensation on employee work discipline in the General Section of the Regional SecretariatCompensation and employee discipline in the office of the General Section of SETDA Kab. Pandeglang is categorized as good. The effect of Compensation on employee work discipline is 62% and the rest is influenced by other factors, it can be in the form of sanctions for employees who do not comply with the rules and create a conducive office atmosphere.